2000
DOI: 10.1073/pnas.97.20.10917
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for monitoring T cell responses to NY-ESO-1 in patients with any HLA class I allele

Abstract: NY-ESO-1 elicits frequent antibody responses in cancer patientsN Y-ESO-1 is a member of the cancer͞testis family of genes (1). Expression of NY-ESO-1 in normal tissues is limited to germ cells, but in cancer, NY-ESO-1 is expressed in a broad range of different tumor types. NY-ESO-1 was discovered by serological analysis of a recombinant cDNA expression library obtained from an esophageal cancer (1). NY-ESO-1 is one of the most immunogenic tumor antigens defined to date, eliciting a humoral response in nearly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 45 publications
1
90
0
Order By: Relevance
“…Recombinant rV-NY-ESO-1 and rF-NY-ESO-1 constructs were obtained from Therion Biologics Corporation (Cambridge, MA) (26).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant rV-NY-ESO-1 and rF-NY-ESO-1 constructs were obtained from Therion Biologics Corporation (Cambridge, MA) (26).…”
Section: Methodsmentioning
confidence: 99%
“…NY-ESO-1 elicits a combined Ab and T cell response (28). Several epitopes of NY-ESO-1 presented by HLA class II molecules (29 -32) and HLA class I molecules (28,33,34) have been identified. Previous work from our group has shown that priming of HLA-A2 (A2) transgenic mice with plasmid DNA and recombinant vaccinia virus encoding the A2-restricted epitope NY-ESO-1 157-165 elicits a strong NY-ESO-1 157-165 -specific CTL response (35).…”
Section: Intravenous Injection Of a Lentiviral Vector Encodingmentioning
confidence: 99%
“…This combination of restricted normal tissue expression, spontaneous immunogenicity and frequent tumor expression has pushed MAGE and NY-ESO-1 to the forefront of tumor immunotherapy as attractive targets for cancer vaccines, 1,8 and multiple clinical trials using these 2 antigens have been carried out, with promising results observed in some studies. [9][10][11][12][13][14][15][16][17] Following the initial identification of MAGE and NY-ESO-1 families, more than 80 gene or gene families have been described as CT or CT candidate genes in the literature. These genes have been organized and annotated into a CT database by the Ludwig Institute for Cancer Research (http://www.cancerimmunity.org/ Ctdatabase/ and http://www.cta.lncc.br).…”
mentioning
confidence: 99%